Bankruptcy Prediction Models for the Banking Sector of Europe - Kazakevičiūtė, Goda; Budrionytė, Ramunė (Buhalterinės apskaitos teorija ir praktika, 2019)
The global financial crisis has hit the global business and society hard and has caused a mistrust in the monitoring and control of the banking sector a decade ago. The distrust encouraged supervisory authorities to reinforce the bankruptcy preventive measures, that are being developed to prevent or mitigate the negative effects of the new crisis. The development and permanent application of reliable bankruptcy prediction models are the part of such preventive measures. The aim of the study was to create a universal straightforward bankruptcy prediction model for the European banking sector, based on the analysis of financial ratios. The study examines the scholarly literature and deploys the theoretical methods of comparative analysis, critical evaluation, systematisation, generalisation. The empirical research involves expert assessment method, analysis of financial statements, data collection, structuring and modification, modelling: binary logistic regression, correlation, graphical representation of data, ROC curve. Research and results: based on selected 24 variables (ratios), five binary logistic regression models were created. The accuracy was tested on the ROC curve, together with the comparison of II type errors, which were made while predicting bank’s failure 1 year and 2 years before the distress. Main findings were: when models where validated and their II type errors were compared, the conclusion was made that model Z5 is the most suitable for predicting bankruptcy for the European banking sector. The accuracy to identify failing banks 1 year before the distress was 78.57%.JEL: F 37, G2, G3
Keywords: bankruptcy forecasting models for banks; European banks; financial ratios